The relationship between social media participation and employees' performance at Lembaga Tabung Haji Johor Bharu, Johor Darul Takzim / Fatin Liyana Mohammad @ Mokhzani - Mohammad @ Mokhzani, Fatin Liyana (Faculty of Business and Management, 2018)
The purpose of this research was to determine the relationship between social media participation and employees' job performance at Lembaga Tabung Haji Johor Bharu. A set of 30 questionnaires were distributed to the respondents at Lembaga Tabung Haji Johor Bharu and they were given a week to complete the questionnaires. Elements of social media participation which act as independent variables involved in this research were communication skills and knowledge sharing while the job performance acts as dependent variable (DY). Statistical Package for Social Science (SPSS) version 23.0 was used to analyze the data. The results of significant and positive correlation between communication skills and job performance and between knowledge sharing and job performance has been displayed in this research. The research hypothesis were accepted as researcher has successfully identified that there was a significant linear relationship between the communication skills, knowledge sharing and job performance. Last but not least, researcher has mentioned some of recommendations for the organization and suggestions for future research that will hopefully bring many benefits to the organization and future researchers as well as readers.